EFEK MEDIASI MINAT BELI PADA KEPUTUSAN PEMBELIAN MAKE-UP - Bakhtiar, M. Rifki; Sunarka, Puji Setya (Fakultas Ekonomi, Universitas Semarang, 2023)
High consumer beautification and high market share potential lead to competition in the make-up industry. The Ministry of Industry stated that the country's make-up industry reached more than 760 companies in 2017 and is targeting significant growth in the make-up industry in 2018-2020. To support this growth, this research was conducted to find out what factors must be considered to increase people's make-up purchases. The focus of this study is the analysis of beauty vloggers, product variations, halal labels, and brand awareness in purchase decisions, using consumer buying interest as a mediator in the makeup industry. Beauty vloggers are presented in this study because, currently many people work as beauty bloggers and they are much loved by the public. Beauty vlogger is a marketing medium that can build positive brand associations through repeated claims about brand attributes and the benefits they offer. Purposive sampling was used in this research sample. Questionnaire: count 100 respondents who meet the requirements as a sample. Multiple linear regression with SPSS 25 was used as a data analysis tool. The results showed that beauty vloggers, product variety, and brand awareness had a positive effect on purchase intention, while the halal label had no effect. Purchase intention, beauty vloggers, and brand awareness have a positive effect on purchasing decisions, while product variations and halal labels have no effect. The path analysis test shows that buying interest is not able to mediate the influence of beauty vloggers, product variations, halal labels, and brand awareness on purchasing decisions